MEDIA MASSA DAN ISLAM POLITIK; Analisis Isi Pemberitaan Harian Kompas dan Harian Republika tentang Penyerang Ahmadiyah, Penyerangan Gereja Temanggung, Penyerangan Syiah Sampang, dan Berita Partai-partai Islam setelah Verifikasi KPU - Budi Ayani (Universitas Islam Negeri Imam Bonjol Padang, 2013)
n the perception of mass media, the political Islam discourse has been defined by the relationship of the media,discourse, and audiences who had been identified before such as the media redactional wisdom. This researchto respond what became the background of political Islam discourse brought by mass media such as: HarianKompas News and Republika about Ahmadiyah Aggression in Cikeusik, Church Aggression in Temanggung,the aggression of Syiah in Sampang, and other parties news verified by General Election Commision (KPU)on January 2013. This research was completed by describing and explaining comprehensively. The way thatit used is media politic. By content analyses in critical discourse analyze paradigm, it has been found thatboth of these national medias affect the reader. Republika always serves political Islam discourse into islamicdynamics, but Kompas gives it into Indonesianity dynamics in Bhineka frame and nation unity. Both ofthese mass medias focus on government participation to handle politic Islam cases in Indonesia. The researchsignification is to become kritical material for readings of political Islam dicourses in mass media and to beable to be used as addition analysis today.